K-State Turfgrass Research 1997 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 1997)
With our staff at full strength, several new research projects have been initiated for the 1997 season. As always, we are anxious to hear your suggestions for research that can be done to improve our ability to maintain healthy turf in Kansas.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 788; Kansas Agricultural Experiment Station contribution; no. 97-400-S; Turfgrass; Environmental stress; Pest management; Creeping Bentgrass; Bluegrass; Ryegrass; Fescue